Effect of non-steroidal anti-inflammatory drugs on radiographic spinal progression in patients with axial spondyloarthritis: results from the German Spondyloarthritis Inception Cohort. Issue 10 (29th March 2012) - Poddubnyy, Denis; Rudwaleit, Martin; Haibel, Hildrun; Listing, Joachim; Märker-Hermann, Elisabeth; Zeidler, Henning; Braun, Jürgen; Sieper, Joachim
Abstract : Objective: To investigate the influence of non-steroidal anti-inflammatory drugs (NSAIDs) intake on radiographic spinal progression over 2 years in patients with ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (SpA). Methods: 164 patients with axial SpA (88 with AS and 76 with non-radiographic axial SpA) were selected for this analysis based on availability of spinal radiographs at baseline and after 2 years of follow-up and the data on NSAIDs intake. Spinal radiographs were scored by two trained readers in a concealed randomly selected order according to the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) system. An index of the NSAID intake counting both dose and duration of drug intake was calculated. Results: High NSAIDs intake (NSAID index≥50) in AS was associated with lower likelihood of significant radiographic progression defined as an mSASSS worsening by ≥2 units: OR=0.15, 95% CI 0.02 to 0.96, p=0.045 (adjusted for baseline structural damage, elevated C reactive protein (CRP) and smoking status) in comparison with patients with low NSAIDs intake (NSAID index<50). This effect was most pronounced in patients with baseline syndesmophytes plus elevated CRP: mean mSASSS progression was 4.36±4.53 in patients with low NSAIDs intake versus 0.14±1.80 with high intake, p=0.02. In non-radiographic axial SpA, no significant differences regarding radiographic progression between patients with high and low NSAIDs intake were found. Conclusion: A high NSAIDs intake over 2 years is associated with retarded radiographic spinal progression in AS. In non-radiographic axial SpA this effect is less evident, probably due to a low grade of new bone formation in the spine at this stage.